Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan PT. Unilever Indonesia Tbk Periode 2015-2019 - Uswatun Fadillah Marpaung; Endang Mahpudin (Jurnal Ilmiah Wahana Pendidikan, 2023)
"An Analysis of Financial Statements to Assess the Financial Performance of Pt Unilever Indonesia Tbk for the 2015-2019 Period". This study aims to describe and find out how the financial performance and financial statements of PT. Unilever Indonesia Tbk. The problems studied are the condition of financial performance and financial statements of PT. Unilever Indonesia Tbk. from 2015 to 2019. The analytical method used is financial ratio analysis which includes liquidity ratios, solvency ratios, activity ratios, and profitability ratios using the time series analysis method for companies. This research is a quantitative and qualitative research with a descriptive approach using calculations of quantitative data in the form of year-end closing financial reports (secondary data) from 2015-2019. Overall, the results of the analysis show that the financial condition of PT. Unilever Indonesia Tbk. fluctuate but the financial performance of PT. Unilever Indonesia Tbk. can be said to be very good in its efficiency. This means that the company has a good level of financial performance, so that it can attract investors to invest in shares.